Gender Diversity and Sustainability Performance of Companies Listed on the IDX - Surbakti, Lidya Primta; Sari, Rida Perwita (International Journal of Social Science and Business, 2024)
This study investigates the impact of female directors and commissioners on the sustainability performance of companies listed on the Indonesia Stock Exchange (IDX). Drawing on previous research, it explores how gender diversity on corporate boards influences sustainability performance across three dimensions: financial, environmental, and social performance. The sample includes 56 non-financial companies listed on the IDX over the period 2019-2021. To analyze the data, the study employs Ordinary Least Squares (OLS) and regression analysis on panel data samples. The results suggest that increasing the proportion of women on boards leads to improvements in both economic and social performance. Specifically, female board members demonstrate a stronger focus on social and economic issues related to stakeholders than their counterparts on boards of commissioners. This finding highlights the importance of gender diversity in driving better engagement and decision-making within companies. This study contributes to the growing body of literature on gender diversity in non-financial companies and underscores the need for a strategic approach to board composition. It suggests that companies should prioritize the right balance of female members on both boards of directors and commissioners to enhance overall sustainability performance. The practical implication of these findings is that policymakers and regulators should actively encourage gender diversity, as it can lead to more sustainable and responsible corporate practices.